Development of a Survey Instrument for Measuring Firefighter Ergonomic Factors in Hose Rolling Activity A Pilot Study - Nurul Nafisah, Abdul Karim; Salwa, Mahmood; Helmy Mustafa, El Bakri; Ismail, Abdul Rahman; Mohd Fahmi, Badulrudin; Norazlianie, Sazali (Semarak Ilmu Publishing, 2024)
The hose is an essential piece of equipment for firefighters on the job. Flaking, roll and coil, dutch roll, and figure eight are all methods of rolling the hose. Hose rolling requires a combination of uncomfortable postures, repetitive motions, and forceful exertion, which can be stressful on firefighters' bodies. Several firefighters' work duties include the application of high physical loads to the human body. High force demands require muscles to work harder, increasing tiredness and the risk of Musculoskeletal Disorders (MSDs). The main objective of this paper is to present the development and validation of a survey instrument for measuring firefighter ergonomic factors in rolling activity for a pilot study. A set of survey instruments was developed, which consisted of four sections: the demographic profile of the respondent, the Cornell musculoskeletal discomfort survey (CMDQ), hose rolling activity among firefighters, and the design criteria for ergonomic hose rollers. The survey instruments's content was obtained from extensive literature research and expert input. A pilot study was conducted at Pagoh Fire Station. The reliability and validity of the instrument were determined through Cronbach’s alpha, face validity, and content validity. Cronbach’s alpha values for each section of the survey instruments range from 0.741 to 0.928, while the value for Cronbach’s alpha for all 26 standardized items is 0.854. Finally, the findings suggested that this instrument had appropriate reliability and validity to accomplish its aims. The survey instrument is now complete and ready for the distribution of larger amounts of data.